Secure chaotic dual encryption scheme for H.264/AVC video conferencing protection. Issue 1 (1st January 2018) - Khlif, Naziha; Masmoudi, Atef; Kammoun, Fahmi; Masmoudi, Nouri
Abstract : This study presents a chaos‐based crypto‐compression scheme to protect the H.264 advanced video coding (AVC) used for the applications of video conference. To this end, a selective encryption approach was adopted. The authors proposed to encrypt the inter‐prediction, the intra‐prediction and the context adaptive variable length coding. The format compliance and compression ratio are conserved. Their encryption method is based on two piecewise linear chaotic maps for pseudo‐random bit generators. The first is considered as a decision module to choose either to encrypt or not, whereas the second is used for the encryption. The proposed encryption techniques were developed and discussed, and their experimental results indicate that the scheme is secure and very efficient according to the computing times. Moreover, it is suitable for real‐time application and convenient for all the H.264/AVC profiles or even with other video compression standards.